Fabricating and Properties of Rifampicin-loaded Ethyl Cellulose Composites Via Electrospray - LI, Xi; CHEN, Yanwen; LI, Hong; DING, Jiahao; WANG, Ya; MO, Jin; ZHOU, Mi; LI, Yaning; LIN, Qiuhan; WANG, Boliang (Studia Universitatis Babeș-Bolyai Chemia, 2024)
Rifampin (Rif) is usually applied as first-line anti-tubercular drugs but has limited bioavailability. Herein, Rif-loaded ethyl cellulose (EC) composites was designed and fabricated by electrospray to improve therapy effectiveness and duration. A novel stable disk-like drug delivery system was prepared, and characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, differential scanning calorimetry (DSC), thermogravimetric (TG) analysis as well as in vitro release tests in phosphate buffer solution (PBS) at pH= 4.0 and pH= 7.4. The SEM results suggested EC/Rif composites had uniform circular surface and particle size distribution with an average size ranged from 7.11 µm to 7.37 µm. Rif can be physically and molecularly dispersed and incorporated into the EC matrix, as confirmed by the XRD, FTIR, DSC, and TG results. At pH 7.4, the rate of Rif release in EC/Rif composites improved with the increasing Rif content. For EC/Rif sample with equal mass ratio, the highest cumulative release of Rif reached 64.6% at the end of 24 h, while at pH 4.0 the Rif release was slower to 24.8% at 24h. These results suggested that EC/Rif composites fabricated by electrospray could be a promising strategy for controlling Rif delivery.